Integrative Islamic Education for the Elderly: A Holistic Model from Madrasah Ibnu Mas’ud in Malaysia - Lukman Hakim; Abdul Kodir; Muhd Zulhilmi Haron (The Faculty of Tarbiyah and Teacher Training associated with PSPII, 2025)
Elderly education represents a critical yet frequently overlooked component of lifelong learning, essential for improving the overall well-being of aging populations. This study investigates how Madrasah Ibnu Mas’ud (MIM) in Malaysia implements an integrative educational model designed to address the spiritual, social, and physical needs of elderly individuals. Employing a qualitative case study methodology, data were gathered through interviews, observations, and document analysis. Findings reveal that MIM effectively integrates Islamic religious teachings, including Qur’anic study and hadith, with practical daily activities such as congregational prayers, religious discussions, light physical exercises, and structured social interactions. These comprehensive programs significantly enhance the spiritual growth, physical health, and sense of community among the elderly participants. By balancing religious education with physical and social activities, MIM mitigates common elderly issues such as emotional isolation and social disengagement. This integrative model demonstrates substantial potential for improving the holistic quality of life for older adults. Consequently, this research provides valuable implications for Islamic educational institutions, underscoring the necessity of inclusive elderly educational programs that simultaneously nurture religious fulfilment and physical well-being.